Insecticidal effect of powder and ethanolic extract of Cnidoscolus aconitifolius (Euphorbiaceae) on adults of Callosobruchus maculatus F. (Coleoptera:Chrysomelidae). - HANGNILO, Lydia; GANDA, Haffizou; ZANNOU épouse BOUKARI, Elisabeth Tohouédé (My University, 2022)
Plants with insecticide effect is the main recourse to control cowpea weevil (Callosobruchus maculatus). This study assessed in laboratory, insecticidal effect of various doses of powder (125, 250, 375, 500, 625, 750 and 875 g of powder/kg of cowpea) and ethanolic extract (10%, 15%, 20% and 25% w/v) of Cnidoscolus aconitifolius on adults of the weevil. 10 adult couples of newly emerged weevil were introduced into each jar containing powder-seed or extract-seed mixture at a rate of 16 g healthy cowpea per treatment and per replication. The results revealed that the mortality rate was positively correlated with dose of powder (22.43 to 69.46%) and concentration of ethanolic extract (11.65 to 44.95%) of C. aconitifolius. Emergence rate decreased with dose of powder (12.31 to 5.13%) and concentration of ethanolic extract (19.24 to 8.44%). Infestation and oviposition rate were significantly reduced (Prob. < 0.001) by both extracts of C. aconitifolius. The different results revealed the potential of this plant to reduce the damage of C. maculatus in cowpea in storage. It is therefore possible to consider the use of extracts of this plant for the control of C. maculatus.
Keywords: Cowpea; C. maculatus; C. aconitifolius; Toxicity; Storage